Analisis Strategi dan Sistem Informasi Manajemen dengan Menggunakan Strengths, Weaknesses, Opportunities, Threats (SWOT) Pada Kantor Pos Malang 65100 - Michael Gerrits Kriswanto Remetwa; Yusaq Tomo Ardianto; Nanik Sisharini (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2018)
This study analyzes the strengths, weaknesses, opportunities and threats posed by Post Office Malang 65100 to achieve maximum results in services offered by PT. Pos Indonesian, by identifying all the resources and supporting services of PT. Pos Indonesia and analyze the strategic plan that must be done Post Office Malang 65100 in achieving organizational goals that have been specified. The research categorized as qualitative descriptive uses researchers as a key instrument in this study. Data collection techniques used include interview techniques and documentation of archives and other secondary data published by PT. Pos Indonesian.The result of data analysis with external internal matrix has illustrated the position of Post Office Malang 65100 in position of growth and stability and in SWOT quadrant diagram assessed that Post Office Malang 65100 has opportunity and strength which means can support aggressive growth policy so that it is possible that postal service offered can be expanded its market share, especially to start taking into account the growing development of micro, small and medium enterprises as a new market share of postal services. Capacity building of the employees as one of the main elements for the company and inter-institutional cooperation relationships that have been done or will be done need special attention to maximize the performance of Post Office Malang 65100